Analysis of the Determinants of Economic Growth in the Province of East Nusa Tenggara - Lika, Ernestina; Pangastuti, Diana (Green Publisher Indonesia, 2024)
This study is a quantitative study that examines the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Tax Revenue Sharing on economic growth in East Nusa Tenggara province during the period 2008-2017. Secondary data from the Indonesian Bureau of Statistics (BPS) East nusa tenggara Province were used, with independent variables including PAD, DAU, and Tax revenue Sharing, and the dependent variable was economic growth. The analysis method used is multiple linear regression with the Ordinary Least Square (OLS) technique to determine the relationship between these variables. The results of this study are expected to provide an overview of how much PAD and DAU contribute to economic growth during the research period.